Interstitial lung disease in patients with rheumatoid arthritis: a narrative review - Gloria Candelas Rodríguez; Virginia Villaverde (Exploration of Musculoskeletal Diseases)
Rheumatoid arthritis (RA) is a chronic immune-mediated inflammatory disease of unknown origin. Although it mainly affects joints, it can have extra-articular manifestations, with the lung being one of the most affected organs. The estimated incidence of diffuse interstitial lung disease (ILD) is 4 cases to 4.5 cases/1000 patient-years. The most common forms are usual interstitial pneumonia (UIP) and nonspecific interstitial pneumonia (NSIP; 44–46% and 33–44%, respectively), although there have been reports of cases involving all the histopathologic forms described for the disease. RA-ILD is associated with specific risk factors, such as male sex, older age, smoking, and positive rheumatoid factor (RF) and anti-citrullinated peptide antibody (ACPA) levels. The clinical course of ILD ranges from asymptomatic forms to rapidly progressive disease in a minority of cases. It has been estimated that the risk of death is up to 3-fold higher in patients with RA-ILD than in those without ILD, making RA-ILD the second most common cause of death after cardiovascular disease. Treatment of RA has improved considerably in recent years with the advent of biologics; however, the use of these agents has been restricted in patients with ILD owing to safety concerns. Many doubts continue to surround the treatment of patients with RA-ILD. Therefore, the objective of this review is to examine the current management of affected patients in terms of diagnosis, treatment, and follow-up.